Climate Change Impacts on Agriculture: A Review of Plant Diseases and Insect Pests in Ethiopia and East Africa, With Adaptation and Mitigation Strategies - Alemu Nega (Advances in Agriculture)
Climate change significantly threatens global agriculture, with East Africa, particularly Ethiopia, being highly vulnerable due to its reliance on rain-fed farming. This review investigates the effects of climate change on plant diseases and insect pests, underscoring the urgent need for adaptation and mitigation measures. Ethiopia’s observable climate trends rising temperatures, erratic rainfall, and increased extreme weather events create conducive conditions for the proliferation of pests and diseases, jeopardizing agricultural productivity and food security. Climate change alters the dynamics of plant diseases by affecting pathogen life cycles, enhancing survival rates, and increasing host vulnerability. Insect pests similarly adapt to shifting climates by altering their geographical distribution and life cycles, leading to intensified outbreaks that threaten key crops like coffee, wheat, and maize. Drought-stressed plants are particularly susceptible, intensifying crop losses. Addressing these challenges requires a multifaceted approach, including developing climate-resilient crop varieties, early warning systems for outbreaks, integrated pest management (IPM), and improved irrigation practices. Mitigation is equally essential, advocating for sustainable agricultural methods, agroforestry, and carbon sequestration strategies. In conclusion, climate change poses a significant risk to plant health and food security in Ethiopia and East Africa. Effective adaptation and mitigation strategies are crucial for sustainable agriculture and food security as the region faces a growing population. Further research is needed to fill knowledge gaps and create locally tailored solutions for long-term agricultural resilience.